Sedition hunters: how January 6th broke the justice system - Reilly, Ryan J. (PublicAffairs, 2023)
"The attack on the Capitol building following the 2020 election was an extraordinarily large and brazen crime. Conspiracies were formed on social media in full public view, the law-breakers paraded on national television with undisguised faces, and with outgoing President Donald Trump openly cheering them on. The basic concept of law enforcement--investigators find criminals and serve justice--quickly breaks down in the face of such an event. The system has been strained by the sheer volume of criminals and the widespread perception that what they did wasn't wrong. A mass of online tipsters--"sedition hunters"--have mobilized, simultaneously providing the FBI with valuable intelligence and creating an ethical dilemma. Who gets to serve justice? How can law enforcement still function as a pillar of civil society? As the foundations of our government are questioned, the FBI and Department of Justice are the first responders to a crisis of democracy and law that threatens to spread, and fast. In this work of extraordinary reportage, Ryan Reilly gets to know would-be revolutionaries, obsessive online sleuths, and FBI agents, and shines a light on a justice system that's straining to maintain order in our polarized country. From the moment the police barriers were breached on January 6th, 2021, Americans knew something had profoundly changed. Sedition Hunters is the fascinating, high-stakes story of what happens next" --